HDL and coronary heart disease—novel insights - Landmesser, Ulf (Nature reviews cardiology, 2014)
The association between HDL cholesterol and cardiovascular events, and the potential antiatherogenic effects of HDL particles, are altered in patients with established coronary heart disease. HDL particle composition has, therefore, gained attention after trials of therapies to increase HDL-cholesterol levels did not reduce the risk of an adverse cardiovascular event.